2020
DOI: 10.1111/ajt.15934
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced vascular inflammation skews infiltrating macrophages to a novel remodeling phenotype in a model of transplant rejection

Abstract: I F(ab′) 2), macrophages differentiated by endothelium activated with HLA IgG F(ab′) 2 fragment; M(HLA IgG), macrophages differentiated by endothelium activated with intact HLA IgG; TV, transplant vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 67 publications
(138 reference statements)
3
17
0
Order By: Relevance
“…Although older studies did demonstrate that HLA class I antibodies can directly trigger cytokine secretion from endothelial cells (15,63), our data are in accordance with the study of Wei et al, where HLA class I antibodies did not induce cytokine production directly from endothelial cells derived from aortic rings, but cell-cell contact of monocytes with antibodyactivated endothelial cells was required for cytokine production (57). The observation that this is also true for glomerular endothelial cells used in our experiments, which are more relevant for kidney microvascular injury, is novel.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although older studies did demonstrate that HLA class I antibodies can directly trigger cytokine secretion from endothelial cells (15,63), our data are in accordance with the study of Wei et al, where HLA class I antibodies did not induce cytokine production directly from endothelial cells derived from aortic rings, but cell-cell contact of monocytes with antibodyactivated endothelial cells was required for cytokine production (57). The observation that this is also true for glomerular endothelial cells used in our experiments, which are more relevant for kidney microvascular injury, is novel.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study by Wei et al. ( 57 ) studying monocytes and DSA-mediated injury of endothelial cells, using F(ab′)2 alone induced only upregulation of the antigens on the endothelial cells, leading to increased tethering and adhesion of monocytes. Only in the presence of the Fc region was the extra signal for activation of the monocytes provided, inducing cytokine secretion, suggesting that FcyR-mediated signaling is essential for the cytokine production in DSA-mediated injury.…”
Section: Discussionmentioning
confidence: 91%
“…The result found that ABO and HLA incompatibilities could increase the probability of infection-medicated rejection and influence the overall survival both for patient and graft [ 31 ]. Moreover, HLA donor-specific antibodies could induce inflammation, vessel injury and AMR by binding to vascular endothelial cells of the allograft [ 34 ]. As three important members in HLA class I heavy chain paralogues, HLA-A, HLA-C and HLA-G were found to be potentially regulated by miR-23b-3p in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies of cocultured monocytes with HLA class I antibody-activated endothelial cells demonstrated secretion of proinflammatory cytokines. 196,197 This cytokine production can orchestrate the recruitment and activation of deleterious immune cells that perpetuate the rejection process by eliciting direct graft injury or secreting even more cytokines. Among these, CXC chemokine ligand 10 is produced by both endothelial cells and monocytes, and its increase is well associated with ABMR, recruiting both innate CXC chemokine receptor 3 þ NK cells and adaptive CXC chemokine receptor 3 þ T cells.…”
Section: Crosstalk Of Allorecognition Pathways In Kidney Transplantationmentioning
confidence: 99%